2016
DOI: 10.12688/f1000research.9226.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and toxicity studies of pyridinecarboxaldehydes and L-tryptophan derived Schiff bases and corresponding copper (II) complexes

Abstract: Schiff bases and their metal-complexes are versatile compounds exhibiting a broad range of biological activities and thus actively used in the drug development process. The aim of the present study was the synthesis and characterization of new Schiff bases and their copper (II) complexes, derived from L-tryptophan and isomeric (2-; 3-; 4-) pyridinecarboxaldehydes, as well as the assessment of their toxicity in vitro. The optimal conditions of the Schiff base synthesis resulting in up to 75-85% yield of target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It has been shown that there is a dysregulation of copper homeostasis and/or localization in the organism affected by cancer [51,52]. Therefore, copper (II) complexes have received increasing attention for their biological characteristics [10,31,[53][54][55][56][57]. The development of copper-based metal complexes may promise an alternative to the adverse effects and toxicities seen in the traditionally used chemotherapy agent [10,31,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that there is a dysregulation of copper homeostasis and/or localization in the organism affected by cancer [51,52]. Therefore, copper (II) complexes have received increasing attention for their biological characteristics [10,31,[53][54][55][56][57]. The development of copper-based metal complexes may promise an alternative to the adverse effects and toxicities seen in the traditionally used chemotherapy agent [10,31,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and characterization of Schiff base copper complexes have been carried out according to previously described methods [31]. All synthesis procedures were performed under normal atmospheric conditions.…”
Section: Chemical Synthesis Of Schiff Base Copper (Ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of PLT was performed as described previously 17 by condensation of picolinaldehyde (2-pyridinecarboxaldehyde) and potassium salt of L-tryptophan in alcohol solution (ethanol, methanol) in a molar ratio 1:1 at the temperature range 5-25°C. A similar procedure was used for NLT synthesis, which is a condensation product of nicotinaldehyde (3-pyridinecarboxaldehyde) and L-tryptophan potassium salt, and PLP, which is a condensation product of picolinaldehyde (2-pyridinecarboxaldehyde) and L-phenylalanine potassium salt (Figure 1).…”
Section: Synthesis and Characterization Of Plt Ntl And Plp Schiff Basesmentioning
confidence: 99%
“…Our previous studies have demonstrated that Schiff base amino acid derivatives picolinyl-L-phenylalaninate (PLP), picolinyl-L-tryptophanate (PLT) and nicotinyl-L-tryptophanate (NLT) are capable of scavenging free-radicals, elevating the capacities of antioxidant and the immune system in radiation injury, and possessing anticytotoxic, antigenotoxic and antimutagenic properties 16,17 . Based on these results, we suggest that the abovementioned multifunctional compounds may have protective effects against mycotoxins.…”
Section: Introductionmentioning
confidence: 99%